Perceived Control Moderates the Effects of Functional Limitation on Older Adults' Social Activity: Findings From the Australian Longitudinal Study of Ageing. (30th September 2015) - Curtis, Rachel G.; Windsor, Tim D.; Luszcz, Mary A.
Abstract: Objectives: Research has shown that functional limitation is related to reduced social activity in older adults; however, individuals with high perceived control have greater confidence in their ability to achieve outcomes and are more likely to show persistence and employ strategies to overcome challenges. The aim of this study was to examine whether perceived control protects against the negative effects of functional limitation on older adults' social activity. Method: Participants were 835 older adults aged 69 to 103 years at baseline from the Australian Longitudinal Study of Ageing. Multilevel modeling was used to examine baseline and within-person change in functional limitation and perceived control as predictors of 18-year trajectories of social activity. Results: An interaction between baseline functional limitation and perceived control indicated that having greater functional limitation was associated with less social activity and greater decline over time for those with lower perceived control, but not for those with higher control. Within-person change in functional limitation was not reliably associated with social activity. Discussion: This study highlights the importance of perceived control as a protective psychological resource and may have implications for developing interventions aimed at enabling older adults to maintain their social activity as they experience functional decline.